ANALISIS MISKONSEPSI BELAJAR MAHASISWA DALAM MENYELESAIKAN MASALAH PADA MATA KULIAH ANALISIS REAL POKOK BAHASANBARISAN BILANGAN REAL - Fitri Apriyani Pratiwi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
The aim of this research was to describe the analyzed misconceptions in solving the sequence of the real number. This research used the descriptive research method with the qualitative explorative approach. The subjects of the research were 12 students 2013 A Program Study Of Education Mathematics, four students category of high value, four students category of medium value, and four students category of low value. The instruments used to gather data of worksheet for problem solving and interview guidelines. The data were task-based interview on the learning material of real analysis problems.They were validated by using the time triangulation and the reference fulfillment. Identification of misconceptions was conducted using Technique of Response Index (CRI) developed by Saleem Hasan with the way of tests. Analysis data this report is written with use the model miles and huberman.The result of the research are as follows: 1) the average capability understanding the concept of students on the sequence of the real number is 67,53%, 2) based on the analysis of CRI based on the criteria answer students, 16,67% (indicators 2), 16,67% (indicators 3), 8,33% (indicators 4) is students were do not know the concept (lucky guess); 25% (indicators 1), 8,33% (indicators 2), 25% (indicators 3), 16,67 (indicators 4), 16,67% (indicators 5), and 66,67% (indicators 6) is students control the concept and reasonable; and 41,67% (indicators 1), 25% (indicators 2), 33,33% (indicators 3), 41,47% (indicators 4), 50% (indicators 5), and 33,33% (indicators 6) is happened misconceptions of students. Keywords: analyzed misconceptions, problem solving real analysis, and sequence of the real number